Teacher’s Perceives on the Implementation of Genre-Based Approach in Teaching Writing - Anjar Nur Cholifah; Reza Pustika; Ardesia Winanta (Hasanuddin University, 2022)
The present study was focused on the teacher’s perceives on the implementation of genre-based approach (GBA) in teaching writing in one of senior high schools in Surakarta, Central Java, Indonesia. The objectives of this study are to explain; 1) The teacher’s perceptions on the practice of the genre-based approach in teaching writing, 2) the matters faced by English teacher, 3) the solutions regarding the problems faced by the teacher. This research was qualitative. The data were collected by implementing questionnaire and interview. The sample of this study was one teacher in Surakarta by using purposive sampling technique. Writers used a model of triangulation process consisting of data reduction, data display, and conclusion to collect and analyze the data. The results showed that; 1) the teacher had positive perception using GBA in teaching writing, 2) there were problems faced by the teacher such as the ease of internet access so that the students could not show their own ideas, and 3) the teachers’ suggestion was that the teacher should be up to date with the newest topic and give motivation to the students to express their own ideas.